2016
DOI: 10.1007/s11695-016-2155-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Adherence to Empiric Vitamin/Mineral Supplementation and Related Nutrient Deficiencies After Roux-en-Y Gastric Bypass

Abstract: Compared to previous reports, we found a lower prevalence of micronutrient deficiencies and excellent patient-reported adherence to a standardized multivitamin/mineral and vitamin B regimen. Continued prevalence of vitamin D deficiency prompts consideration of standardized vitamin D supplementation after RYGB. Anemia and iron deficiency were observed at lower rates than previously reported, but were more common in men compared to women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
3
22
0
1
Order By: Relevance
“…There is a high incidence of iron deficiency anaemia following bariatric surgery because of low dietary iron intake, reduced intestinal absorption and, for some women, menstruation 15,18,19,35–37,41,57–60,72–74,85–94 …”
Section: Postoperative Care and Biochemical Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a high incidence of iron deficiency anaemia following bariatric surgery because of low dietary iron intake, reduced intestinal absorption and, for some women, menstruation 15,18,19,35–37,41,57–60,72–74,85–94 …”
Section: Postoperative Care and Biochemical Monitoringmentioning
confidence: 99%
“…Vitamin B12 absorption is adversely affected by SG, RYGB and BPD/DS as it requires an acidic environment and presence of intrinsic factor produced by the gastric parietal cells 95 . Many people have about 2‐year stores of vitamin B12; therefore, deficiency may present several years after surgery 15,18,19,40,41,47,57–59,65,73,86–89,92,93,96 . Vitamin B12 deficiency impacts adversely on the haematopoietic and nervous systems and may result in megaloblastic anaemia and irreversible neuropathies 95 .…”
Section: Postoperative Care and Biochemical Monitoringmentioning
confidence: 99%
“…Zarshenas et al reported about an inconsistent adherence of MVS intake after bariatric surgery (5) . Many other studies have shown that long-term adherence of bariatric patients to MVS intake is poor (10,(12)(13)(14)(15)(16)(17)(18) . However, it is unclear which factors contribute to patient Abbreviations: LRYGB: laparoscopic Roux-en-Y gastric bypass; LSG: Laparoscopic sleeve gastrectomy; MVS: multivitamin supplementation; OAGB/MGB: One Anastomosis/Mini-Gastric Bypass adherence in taking MVS.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are therefore advised lifelong micronutrient supplementation [5][6]. However, adherence to these recommendations can be poor [7][8][9].…”
Section: Introductionmentioning
confidence: 99%